“Plan de reactivación de turismo cultural en el cantón Quevedo, provincia de los Ríos, año 2021” - Tomalá Macías, Lisbeth Solange (2021)
This research work was conducted in the canton of Quevedo, belonging to the province of Los Ríos, in order to develop a plan for the reactivation of cultural tourism, due to the little cultural knowledge that the inhabitants have; a diagnosis of the cultural attractions that the canton has was made, where 35 attractions were identified; 19 are tangible cultural attractions and 16 are intangible cultural attractions. The preferences towards cultural tourism of the inhabitants of the canton were determined and 386 surveys were applied, resulting in 87.75% know the cultural attractions of Quevedo, 72.28% would visit the attractions with their families, 52.85% are willing to pay from $1 to $5 to access the attractions and 17.54% consider that the creation of a cultural tourism center in Quevedo would be a good idea, 54% consider that the creation of a blog is necessary to obtain information on the canton's cultural sites. As a third objective, a cultural reactivation plan was developed, establishing three programs where in each program three projects were developed with their goals, activities, responsible parties and budget, resulting in the development of a cultural tourism reactivation plan that would help strengthen local culture, cultural knowledge, and contribute to tourism and economic development of the population. Key words: Cultural tourism, tangible cultural attractions, intangible cultural attractions, reactivation plan.